Analisis Spasial Perubahan Penggunaan Lahan Untuk Mitigasi Bahaya Lahan Kritis di Kabupaten Manokwari - Siti Hadjar Kubangun; Kati Syamsudin Kadang Tola; Samsul Bachri (Agrotek, 2019)
Land degradation is the result of land use or utilization that exceeds the capacity of the land, which will cause critical land. The impacts that occur due to critical land include land degradation in the quality of soil properties, decreasing conservation and production functions, as well as affecting the social and economic life of the people who use the land. This study aimed to reduce the hazard of critical land, based on modeling changes in land cover/use using the Artificial Neural Network (ANN) method. The results of this study indicated that land classified as dangerous to become critical land includes sloping land with converted land cover/use. Reducing the risk of critical land hazard can be done by using land that is in accordance with the ability of the land, by following the rules of soil and water conservation, as well as the role of the government in conserving upstream areas that are oriented towards regional spatial patterns.